The relationship between serum total testosterone and free testosterone levels with serum hemoglobin and hematocrit levels: a study in 1221 men. (1st October 2016) - Shin, Yu Seob; You, Jae Hyung; Cha, Jai Seong; Park, Jong Kwan
Abstract: Objective : To investigate the relationship between serum total testosterone (TT) and free testosterone (FT) levels in men with anemia. Methods : We reviewed the records of 1221 subjects between March 2009 and December 2014. All the subjects' blood samples were drawn for TT and FT assays. Their serum hemoglobin (Hb) and serum hematocrit (Hct) levels were measured. The primary objective of our study was to investigate the association between TT and FT levels with Hb and Hct levels. Results : The mean age was 59.82 ± 12.71 years. The mean TT and FT levels were 4.54 ± 2.02 ng/mL and 10.63 ± 3.69 pg/mL, respectively. The mean Hb and Hct levels were 14.72 ± 1.34 g/dL and 43.11 ± 3.75%, respectively. Subjects with low TT (<2.35 ng/mL) had low Hb and Hct levels ( p  < 0.001, p  < 0.001, respectively). TT was positively associated with FT, Hb, and Hct. TT and FT levels were significantly lower in older men. Conclusions : Subjects with low TT and FT levels had low Hb and Hct levels. This suggests that TT and FT play a significant role in erythropoiesis. Testosterone replacement therapy may be effective in men with hypogonadism to reduce the incidence of anemia.